Desenvolvimento de dispersões sólidas e membranas baseadas em praziquantel-poli(álcool vinílico) na terapêutica de esquistossomose - Silva, Vanessa Bezerra da (Universidade Federal de São Carlos, 2021)
Schistosomosis is a parasitic disease considered neglected and endemic in 75 countries. It is estimated that 240 million people are infected and 700 to 800 million people are at risk. Despite that, there is no effective vaccine. Therefore, oral medications continue to be used a lot. Praziquantel (PZQ) is the drug mostly used in this case, however it has low solubility in water and is extremely bitter, making it difficult for children between 3 months and 6 years keep the treatment. Solid dispersion (SD) is a very useful pharmaceutical technology to increase dissolution, absorption, bioavailability and, consequently, the efficiency of a drug and also mask flavors. In order to study the interactions between praziquantel (PZQ) and poly(vinyl alcohol) (PVA), SDs and membranes were prepared and characterized in terms of their microstructure, swelling, release and dissolution. The results show that the crystalline structure is not modified with freeze-thaw cycles and the drug is an obstacle to crystals formation. The swelling measurements show that, for membranes, the amount of PZQ does not influence the sample’s swelling. The XRD shows that the position of PZQ’s peaks is in accordance with the diffraction patterns of the racemic form and that the drugs’ peaks overlap the PVA bands. The infrared spectroscopy shows that for membranes it is clear that the more PZQ in the sample, the smaller is the C–H ring bonds movement, suggesting that the interaction between the polymeric matrix and the drug is given through interactions within the rings in addition to the hydrogen bonds. For the DSs, however, the change between the polymer-drug proportions analyzed is not clear. As for the release, the DS with the highest release for all tested pHs is the sample with a 1:2 ratio (PZQ: PVA) and placed in the Turrax at 20,000 rpm, showing that the processing is important.
Development of solid polymeric dispersion based on praziquantel-poli(vinyl alcohol) system in schistosomosis therapeutics
Keywords: Esquistossomose; PVA; PZQ; Schistosomiasis; Spray dryer; CIENCIAS EXATAS E DA TERRA::QUIMICA